Dental health and alimentation among the Quintana Roo Mayas: Coastal and inland sites of the classic–postclassic periods. Issue 6 (21st August 2015) - Ortega‐Muñoz, Allan; Gurri, Francisco D.; Ortega‐Muñoz, Allan
<x xml:space="preserve">Abstract</x> Objectives The goal of this study is to compare both dental and skeletal stress indicators of the Classic and Postclassic coastal and inland sites of the State of Quintana Roo, Mexico. The hypothesis is that coastal populations will show osteo and dental pathologies characteristic of a primarily marine food source combined with a diet of horticultural resources. This kind of alimentation provides people with less environmental stress and therefore a better health status. However, over time, in the Postclassic period, the health conditions deteriorated among both coastal and inland inhabitants, according to the hierarchization of the society, militarization, and commercial activities of all the coastal sites. Methods The sample was drawn from 19 sites (196 individuals of both sexes) from the east coast of the Yucatan Peninsula, as well as from inland localities within the boundaries of Quintana Roo. Both dental and osteological stress indicators were analyzed, and crosstabs were applied for absolute and relative frequencies and their corresponding χ2 and F Fisher analyses. The osteopathological index of the coastal and inland sites of the Classic period were compared over time between the Classic coastal inhabitants and the Postclassic coastal inhabitants so as to understand how life conditions changed over time. The Mantel‐Haenszel odds ratio, with the crosstabs controlling for sex (males and females), was also carried out. Results There are low frequencies of dental pathologies and anemia present in both the coastal and inland populations of Quintana Roo in the Classic and Postclassic times. Only the presence of periostitis is highly common in both types of site, and this is the only indicator with significant differences. The dental pathologies, anemia and periostitis, in general, present a slight upward trend in both the coastal and inland populations over time. The coastal populations have fewer frequencies of the above than the inland sites whilst, in the Postclassic period, both the coastal and inland sites register increased frequencies of all the indicators. Linear enamel hypoplasia (LEH) is the only indicator that does not follow this tendency. Conclusions The analyzed indicators are in accord with the general tendency reported in the literature. The results revealed a general trend whereby the Classic inland sites display poorer life conditions than the Classic coastal sites. In the Postclassic period, this pattern changed because the frequencies of all stress indicators increased. The explanations regarding this tendency are related to the differential access to food resources between regions; coastal people had a varied diet and better sources of protein, taking into account the culture of alimentation, the type, and the sources (in general, fish) that have an important impact on the absorption of micronutrients and therefore greater impact on local health conditions. Also, it is plausible that they were able to access imported food through commerce (such as meat and vegetables/corn). The decline in health of the coastal people in the Postclassic period was probably associated with social stratification, increasing militarism, changes in the economic corpus, new pathogens, and the decline of the power structures prevailing throughout the Classic period. Am. J. Hum. Biol. 27:779–791, 2015. © 2015 Wiley Periodicals, Inc.